Comparison of the accuracy of a free 3D camera system with the Ariel performance system. Issue 6 (2nd November 2021) - Miranda-Oliveira, Paulo; Branco, Marco; Fernandes, Orlando J.; Santos-Rocha, Rita
ABSTRACT: The aims were: (1) to determine the accuracy and time-consuming of the automatic digitalization feature of 3D motion analysis systems; and (2) to determine the reliability of the 3D position when a football player performed a hard kick with spin. Four high-speed cameras (Casio ZR200 (512x384)) with a 240 Hz field rate were used. Automatic scanning of the Kinovea® and APAS® software was used. The accuracy was determined through mean absolute error, maximum absolute error, mean standard deviation of absolute error, and the variability values. The reliability was calculated with the Intra-Class Correlation. The mean absolute error (3.62 to 3.78 mm), maximum absolute error (9.09 to 11.61 mm), mean standard deviation of absolute error (0.01 to 0.59 mm), variability values (<1 mm), and the auto-digitalization time (16 to 31 minutes) were calculated and were within the values obtained in the literature. The reliability was determined with the Intra-Class Correlation, and the results were higher than 0.90, warrantied a high consistency for chosen software. The accuracy and the reliability intra-operator were determined, and the results indicated that it is possible to apply the free 3D camera system, with consistency in free-kick analysis.